Endokarditis ob elektrodi srčnega spodbujevalnika - Lejko-Zupanc, Tatjana (Zdravniški vestnik, 2005)
Background. To describe clinical picture, treatment and outcome of the diseasein patients with pace-maker related endocarditis. Methods. All the patients fulfilling the Duke patomorphological and clinical criteria for infective endocarditis on pace-maker wire or near it are included. Clinical and demographic data are recorded as well as the time since the implantation of pacemaker, site of infection, portal of entry, causative agent, size and localization of vegetation, mode of operation and outcome of the disease. Results. Since the year 1984 10 episodes of paced-maker-related endocarditis in 9 patients (8 males, 1 female) were treated at the Department of InfectiousDiseases and that represents 2,5% of all episodes of infective endocarditis treated at the department. The causative micro-organisms were isolated in 9 out of 10 episodes, mostly there were coagulase negative staphylococci. One patient died before the operation and another patient afterthe operation. Overall moratlity was 20%. Eight out of 9 patients were operated. Complete paced-maker system or only retained leads were extracted. None of the patients who survived the operation had a relapse of the disease. Conclusions. Pace-maker related endocarditis is rare. Complete cure is usuallyimpossible without combined surgical therapy and long-term antibiotic treatment.
Keywords: Adverse Effects; Cardiac Pacing, Artificial; Diagnosis; Drug Therapy; Echocardiography; Ehokardiografija; Electrodes, Implanted; Elektrode implantirane; Endocarditis, Bacterial; Endokarditis bakterijski; Srčno vzpodbujanje, umetno; Treatment Outcome; Zdravljenje, izid